Zero Waste Innovation PKM: Utilization of "Talas Togog" towards Food Security in the Pkk Group of Batuan Village, Gianyar-Bali - Muliarta, I Nengah; Ni Luh Putu Putri, Setianingsih; Rustini, Ni Made; Pranajaya, I.G.M. Raditya Abimanyu; Adol, Ewaldus; Namu, Fransico Mario (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Taro Togog" has a high nutritional content and has the potential to be processed into various economically valuable food products, namely tubers and stems, applying the principle of zero waste, and producing innovative products such as taro flour and chips. The purpose of the community service is to increase production capacity and product quality to support local food security. Issues raised include production efficiency and product quality of Taro Togog, so that it can attract the younger generation to consume and preserve local food. Thus, relevant and straightforward innovations can have a significant impact on food security at the community level. Through training and mentoring, the Batuan Village partner group has the knowledge and skills to process waste into products with market value. This not only reduces environmental problems by implementing the zero waste concept but also increases local food independence. Contribution to Sustainable Development Goals (SDGs):SDG 2   : Zero HungerSDG 12 : Responsible Consumption and ProductionSDG 17 : Partnerships for the Goals